Spinal cord compression by multiple cysticercosis - Lopez, Sebastian (Surg Neurol Int, 2019)
BACKGROUND: Neurocysticercosis (NCC) is the most common parasitic infection involving the central nervous system in endemic areas. Notably, spinal involvement occurs in only 0.7%–3% of patients. CASE DESCRIPTION: A 58-year-old female presented with progressive spinal cord compression attributed to multiple cystic intradural extramedullary thoracic lesions. She underwent laminectomy at two separate thoracic levels; this involved excision of the upper T4–T6, and just exploration of the lower T9–T11 lesions. One year postoperatively, she exhibited a residual paraparesis. CONCLUSION: Spinal NCC must be considered among the differential diagnostic considerations for patients presenting with spinal intramedullary or subarachnoid/extramedullary cystic lesions. Although they are typically found in endemic regions, those who have traveled to these locations are also susceptible. Even though it is considered a benign condition, spinal NCC may cause permanent and irreversible neurological damage. Public health policies should, therefore, be developed to help control the spread and transmission of NCC.